2005
DOI: 10.1002/acp.1104
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical memory and social skills of men and women

Abstract: This study investigated gender-specific relationships between autobiographical memory (AM) performance and two social skills, namely empathy and assertiveness. One hundred and fourteen male and female students were tested with a questionnaire on AM and two test scales for empathy and assertiveness. The results revealed positive correlations between AM performance and both social skills, thus underscoring the social function of AM. In addition we found several gender differences. Women showed superior AM perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 43 publications
4
57
1
Order By: Relevance
“…Although ASD has a gender ratio of approximately 4:1 (males: females), with ratios of around 6:1 reported for higher functioning samples (Fombonne, 1999), the samples in the current series of studies comprised an equal number of males and females. As gender differences have previously been reported on autobiographical memory tasks (e.g., Goddard, Dritschel, & Burton, 1998;Pohl, Bender, & Lachmann, 2005), the current study investigated the role of gender on autobiographical memory retrieval in ASD. However, there were no significant effects of gender on any of the variables in and 2) were designed for a student sample, the list of goal cues was adapted and extended for the current study, to incorporate a wider range of cues.…”
Section: Discussionmentioning
confidence: 99%
“…Although ASD has a gender ratio of approximately 4:1 (males: females), with ratios of around 6:1 reported for higher functioning samples (Fombonne, 1999), the samples in the current series of studies comprised an equal number of males and females. As gender differences have previously been reported on autobiographical memory tasks (e.g., Goddard, Dritschel, & Burton, 1998;Pohl, Bender, & Lachmann, 2005), the current study investigated the role of gender on autobiographical memory retrieval in ASD. However, there were no significant effects of gender on any of the variables in and 2) were designed for a student sample, the list of goal cues was adapted and extended for the current study, to incorporate a wider range of cues.…”
Section: Discussionmentioning
confidence: 99%
“…H2 Females will achieve higher performance than males in narrative recall and emotional understanding. Previous research has shown that females tend to tell more accurate (Pohl et al, 2005) and detailed (Ross and Holmberg, 1992) narratives, while accounting for the emotions of the narrative characters more often (Buckner and Fivush, 1998;John et al, 2003). Additionally, several authors found that females scored higher in emotional intelligence tests (Collis, 1996;Petrides and Furnham, 2000).…”
Section: Rq1 How Does Interaction Context Impact Children's Informatimentioning
confidence: 99%
“…Yet, Maccoby and Jacklin (1974) concluded that "the two genders show a remarkable degree of similarity in the basic intellectual processes of perception, learning, and memory. " Additionally, females tend to generate more accurate (Pohl et al, 2005), detailed (Ross and Holmberg, 1992), and exhaustive narratives that take social context and emotions into account (Buckner and Fivush, 1998;John et al, 2003). Females are also generally thought to be more emotive both verbally (Smedler and Törestad, 1996) and non-verbally (Briton and Hall, 1995).…”
Section: Individual Differences In Narrative Recall and Understandingmentioning
confidence: 99%
“…This was to assess the role of gender on autobiographical memory and related variables in adults with ASD, in view of gender differences being previously reported on autobiographical memory tasks (e.g., Goddard et al, 1998;Pohl et al, 2005) and in depression (Piccinelli and Wilkinson, 2000). However, the current study found no significant effects of gender on any of the variables in the current study (except depressed mood, as outlined in the results section), in either the ASD or comparison group (p values ranged between .20 and .81; ηp 2 values ranged between .009…”
mentioning
confidence: 99%